NB-SQI: A novel non-binary signal quality index for continuous blood pressure waveforms. (September 2021) - Ignácz, Anna; Földi, Sándor; Sótonyi, Péter; Cserey, György
Abstract: Continuous blood pressure monitoring has utmost importance in healthcare, but is usually realised by invasive arterial cannulation. Non-invasive solutions are starting to become a viable option, but these solutions are more sensitive to sensor placement and patient movement. To support these non-invasive monitoring devices, a continuous signal quality feedback would be advantageous. The aim of this study is to define a non-binary signal quality index (NB-SQI) for continuous blood pressure waveforms that can be used for monitoring devices. The definition of this NB-SQI is based on features derived from the continuous waveform of the cardiac cycle and it tests the abnormality of the signal and measures the normalised deviation of its characteristics from an expected value. The method was validated with a dataset of 20 signals, each 10 s long, and labelled by senior specialists in the field of vascular surgery and anesthesiology. The NB-SQI showed a 0.95 correlation with the labels of the validation set. The tendency of the NB-SQI was tested on generated and measured signals corrupted by generated noises on different levels. The results showed that the NB-SQI gives a quantitative estimation in the higher quality range, and recognises the abnormal and noise corrupted segments. The defined NB-SQI can have a significant contribution to the development of non-invasive continuous blood pressure monitors, but it can also be used in signal processing or signal classification for diagnostic purposes. Highlights: Signal quality has great importance in biomedical signal recording. NB-SQI: A novel non-binary signal quality index for blood pressure waveforms. NB-SQI can be defined using the features of blood pressure waveforms. NB-SQI shows high correlation with the opinion of professionals. NB-SQI can be a great tool for invasive and non-invasive blood pressure monitors. Development of automated sensor placement can also be supported by NB-SQI.